The effect of the AIDS epidemic on widowhood in Northern Uganda - Ntozi, James P. M.; Ahimbisibwe, Fred E.; Ayiga, Natal; Odwee, Jonathan O.; Okurut, Francis N. (The continuing HIV/AIDS epidemic in Africa, 1999)
This paper uses data from a survey in northern Uganda to examine the situation of widowers and widows in the era of AIDS. A high level of widowhood was observed, almost a third being caused by AIDS. Widowhood was more prevalent among women than men. More than one-third of the widows and widowers had remarried or acquired new sexual partners mainly for procreation. Widows also remarried or acquired new sexual partners because they looked healthy. However, the husbands of more than one-third of them had died of AIDS. There were few movements of widowers and widows due to AIDS. Those who had migrated had more children. Other determinants of migration of widows and widowers were age, district of origin and having had children. The AIDS epidemic has been noted as a cause of the current high level of widowhood in Africa (Palloni, Lee and Lamas 1990). It is therefore likely that many of the widowed are HIV infected and will spread AIDS through sexual networking with other groups (Nunn 1989; Maiga et al. 1993; Okeyo and Allen 1994; Taverne 1996). Sexual networking of the widowed may be through widow inheritance, remarriage, casual sexual partners or prostitution. The practice is common among the widowed for social, cultural and economic reasons (Butlerys et al. 1994).
Keywords: AIDS epidemic; widowhood; widowers